DEVELOPMENT OF APPLICATION PROGRAMMING INTERFACE (API) FOR AMIKOM PURWOKERTO HANDSANITIZER (AMPUH) DATA LOGGER VISUALIZATION - Agnis Nur Afa Zumaroh; Trisna Maulida; Hasri Akbar Awal Rozaq; Rona Sepri Ananda; Alif Yahya Syafaat; Imam Tahyudin; Berlilana (Jurnal Teknik Informatika (Jutif), 2022)
The Internet of Things (IoT) of AMPUH adheres to three simple concepts: physical devices with IoT modules, internet-connected devices, and cloud data centers as data storage places. ThingSpeak is an IoT platform that is useful as a cloud-based data logger. Data loggers in the form of primary data or raw data need a web dashboard for data visualization because of not communicative. Therefore, this research has aim to construct API of AMPUH visualization for be used by frontend team. This research converted MATLAB programming language into PHP programming language. The data logger processing uses the powerful programming method because this method is time-efficient and can fix if an error occurs in the system development stage without having to repeat the process from the beginning. The Extreme Programming method has four steps: planning, design, coding, and testing. The processing of data loggers from the ThingSpeak platform uses the Laravel Framework to generate APIs that the frontend team will use. The researcher managed the data logger from ThingSpeak using the Laravel framework to produce several APIs used by the frontend team to visualize the data be interactive and informatively.